2021
DOI: 10.1177/15248380211048445
|View full text |Cite
|
Sign up to set email alerts
|

Violence by Burning Against Women and Girls: An Integrative Review

Abstract: Violence against women and girls by burning is a serious and confronting form of gender-based violence. Often, perpetrators aim to disfigure their victims or cause great pain, rather than kill them. Little is known about the characteristics of females who are subjected to violence by burning. This study aimed to review the literature concerning the prevalence, demographic profile, injury event, contributing factors and health outcomes for women and girls who have experienced burn-related violence. A search acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…There were 170 unmarried unfortunate victims of burns with 2 suffering burns at work place and remaining 168 had burn injuries while they were at home. There were 79 married victims of burns of domestic violence out which just 8 faced burn injuries at the place of work and 71 came across the burn injuries while they were at home 23 . The only widowed burn victim suffered burn injuries at home.…”
Section: Marital Statusmentioning
confidence: 99%
“…There were 170 unmarried unfortunate victims of burns with 2 suffering burns at work place and remaining 168 had burn injuries while they were at home. There were 79 married victims of burns of domestic violence out which just 8 faced burn injuries at the place of work and 71 came across the burn injuries while they were at home 23 . The only widowed burn victim suffered burn injuries at home.…”
Section: Marital Statusmentioning
confidence: 99%
“…The prevalence of self-reported domestic violence against women in India is significantly high, with the reported rate of crime increasing by 53%, over the last 18 years (Dandona et al, 2022). Through the findings of an integrated review, Kornhaber et al (2021) suggested that the victims identified refers to married, low-educated women with high dependency on their partners or families. The perpetrators often attempt to disfigure or inflict pain on their victims, pointing out instances of burn injuries caused by flame or acid, rather than killing them.…”
Section: The Indian Scenariomentioning
confidence: 99%